Поликристаллические материалы на основе микропорошков алмаза, кобальта, никеля и их боридов - Бугаков, В.И.; Поздняков, А.А.; Давыдов, В.В.; Боровиков, Н.Ф.; Миронов, Е.Г. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The work deals with the synthesis of diamond polycrystalline materials at temperatures
T = 1100–1300 °C and pressures P = 4,5–5 GPa with the use of cobalt, nickel and their borides. It
is found that the properties of obtained materials depend on the fractional composition of the initial
diamond powder. The strength characteristics of the investigated polycrystalline materials are superior
to those of the diamond powders AC20 and APB1 of grain size 400/315.